Role of 2-tridecanone and type VI glandular trichome on tomato resistance to Tuta absoluta - Gilardón, Elsa; Pocovi, Mariana; Hernández, Carmen; Collavino, Graciela; Olsen, Ana (Pesquisa Agropecuaria Brasileira, 2001)
The secondary metabolite 2-tridecanone, secreted by the type VI glandular trichomes present in the leaves of Lycopersicon hirsutum L., make it resistant to a great variety of insects, including the tomato pinworm, Tuta absoluta (Meyrick). The 2-tridecanone concentration, the type VI glandular trichome densities and the pinworm infestation degree were evaluated on the Lycopersicon esculentum Mill. susceptible cultivar 'Uco Plata', on the Lycopersicon hirsutum f. glabratum resistant accession PI 134417 and on their F1 and F2. The mean infestation degree with pinworm larvae was significantly higher in 'Uco Plata' than in PI 134417. The 2-tridecanone concentration was significantly higher in the resistant parent, but the presence of this metabolite could only partially account for the resistance (R2 = 8.17%). No significant differences were detected in the type VI glandular trichomes densities between the susceptible and resistant parents. This trait was independent of the 2-tridecanone level and the pinworm infestation degree.